The Role Of Lecturer’s Characteristics Towards Students’ Motivations at Indraprasta Pgri University - Nurhayati Nurhayati; Tri Angkarini (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
The purposes of the research was to investigate the significant role of lecturer’s characteristics both verbal and non-verbal towards students’ motivation in Indraprasta PGRI University. The students were in the third year (semester six) during a period of two months in which this study was conducted. The researchers used survey method in this study. Data collection were conducted by distributing questionnaires both to lecturers and students. The data were processed and analyzed by using statistic descriptive, normality test, linearity test, homogenity test, and hypotheses test. Statistic test uses t test and F test. The research was conducted from second week of March until fourth week of June 2015. The research shows that there is not an effect of lecturer’s characteristics towards students’ motivation with the regression analisis: Y= 43,923 + 0.322 X. Whenever there is a rise in the value of lecturer’s characteristics, there will be a decrease in students’ motivation for 0.322.Key words: lecturer’s characteristics, students’ motivation